O uso do Laboratório de Ensino de Matemática na formação de licenciandos em Matemática - Nayara Katherine Duarte Pinto (2020)
This study of Professional Master in Education and Teaching was part of the research under development “Teaching and Training of Teachers Teaching Mathematics” of the Mathematics Education line, being the result of some reflections and concerns of the researcher when attending the Mathematics Teaching Laboratory of Faculty of Education (LEM FaE). We had as a guiding question of research: What are the reaches and limitations of LEM FaE as support in the planning of classes to be developed under the supervised internship of mathematics in graduation? From this guiding question originated the general objective of this work, which was to analyze the reaches and limitations of the use of LEM FaE as support in the planning of classes to be developed within the supervised internship of Mathematics in graduation. From the formative point of view, we also had as objectives: to contribute to the formation of graduating of the Mathematics course that studied the Pedagogical Practice Analysis and Stage II (APPE II) discipline; bring undergraduates closer to a collaborative practice, involving LEM, and experiences that allowed the contact of undergraduates with Mathematical Education; evaluate, with the participants, the practices developed; produce an Educational Resource that would assist in the construction and enhancement of an LEM. This research was developed according to a qualitative approach. The work plan comprised phases that covered the planning (undergraduates, researcher and supervising teacher), development (by the undergraduates) and evaluation of the lesson plans (undergraduates, researcher and supervising teacher) after the classes with the students of the school. Information recording instruments aiming at the description were: Participant Identification questionnaire; audio recording of activities developed in the meetings; field journal; semi-structured interview conducted separately with each participant after completion of the elaboration and development of the lesson plan; registration of email and message exchanges by the WhatsApp application with survey participants. The data were analyzed from the description of each undergraduates and from the meetings, the evolution of the script of the lesson plan and the evaluation of each participant, highlighting the reaches and limitations in the use of the LEM, the internship and the collaboration between researcher and participants. We ended with an understanding that LEM FaE can be a space that enables knowledge exchange, new learning, experimentation, planning, development and evaluation of activities, thus distancing itself from teaching in the most traditional way, which uses only chalk and blackboard, and does not consider student protagonism. The resource developed was an e-book containing a small theoretical reference about some conceptions of LEM, the LEM in Teacher Training and suggestions of activities and materials that enhance the scope of LEM. In the e-book are some of the lesson plans developed in conjunction with the undergraduates. We consider that the availability of this digital material in the field of Mathematical Education, may broaden the perceptions of the potential use of a Mathematics Teaching Laboratory in the formation of undergraduates.